Prelamination of Neourethra with Uterine Mucosa in Radial Forearm Osteocutaneous Free Flap Phalloplasty in the Female-to-Male Transgender Patient - Christopher J. Salgado; Lydia A. Fein; Jimmy Chim; Carlos A. Medina; Stephanie Demaso; Christopher Gomez (Case Reports in Urology)
Radial forearm free flap phalloplasty is the most commonly performed flap for neophallus construction in the female-to-male (FtM) transgender patient. Urological complications, however, can arise quite frequently and can prevent the patient from urinating in the standing position, an important postsurgical goal for many. Using mucosa to construct the fixed urethra and to prelaminate the penile urethra has been successful in reducing urologic complications, particularly strictures and fistulas. Until now, only buccal, vaginal, colonic, and bladder sites have been described as sources for these mucosal grafts. We present the successful use of uterine mucosa for prelamination of the neourethra in an FtM patient who underwent hysterectomy and vaginectomy at the prelamination stage of a radial forearm phalloplasty. Three months postoperatively, the patient was able to void while standing and showed no evidence of stricture or fistula on retrograde cystogram. These results suggest that uterine mucosa may be used for prelamination of the penile neourethra in patients undergoing phalloplasty.